2014
DOI: 10.4236/ojgas.2014.410046
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of 10 Drug-Refractory IBS Patients Who Respond to Oral Serum-Derived Bovine Immunoglobulin/Protein Isolate (SBI)

Abstract: Aim: The responses of 10 patients with long-standing, symptomatic, intractable drug-refractory histories of irritable bowel syndrome with diarrhea (IBS-D) and with abdominal pain, gas/bloating and distention, termed IBS undefined (IBS-U), were evaluated when administering a medical food product containing serum-derived bovine immunoglobulin/protein isolate (SBI). Methods: Patients in this case series were chosen based on their lack of satisfactory response to a variety of drugs, including antidiarrheal and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…2013]. In addition, case studies of SBI report management in drug-refractory IBS-D patients in real-world settings [Hilal et al . 2014; Weinstock and Jasion, 2014; Good et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013]. In addition, case studies of SBI report management in drug-refractory IBS-D patients in real-world settings [Hilal et al . 2014; Weinstock and Jasion, 2014; Good et al .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, SBI has been shown to reduce symptoms of abdominal discomfort, flatulence, bloating, loose stools and urgency in IBS-D [Wilson et al 2013] as well as loose stools, cramping, urgency, incontinence and nocturnal bowel movements in HIV-associated enteropathy [Asmuth et al 2013]. In addition, case studies of SBI report management in drug-refractory IBS-D patients in real-world settings [Hilal et al 2014;Weinstock and Jasion, 2014;Crawford and Panas, 2015]. Recent case series utilizing SBI in CD and UC patients to achieve clinical remission in patients who were not fully managed by traditional drug therapies [Awad and Jasion, 2015; as well as potential endoscopic remission [Beauerle et al 2015;Awad and Jasion, 2015].…”
mentioning
confidence: 99%
“…Approximately 25-50% of orally administered IgG survives digestion in the stomach and small intestine [18] . In clinical practice, SBI has been used in numerous patients as a therapeutic option to help manage chronic loose and frequent stools in patients as well as patients with IBS-D [26,27] . While SBI may not be effective in all patients, clinical experience would suggest that SBI is safe and effective in many patients with chronic loose and frequent stools.…”
Section: Introductionmentioning
confidence: 99%
“…One patient withdrew due to metallic taste, mouth sore and nausea. In recent retrospective reports of SBI use collected from medical charts, there was approximately a 70% overall response rate to therapy in drug-refractory IBS-D patients [17][18][19][20]. For example, Hilal et al [17] and Good et al [18] reported patients with IBS-D, IBS-M, and IBS with bloating had about 75% overall management of their condition.…”
Section: Discussionmentioning
confidence: 99%
“…In colitis animal models, SBI consumption led to decreased proinflammatory cytokine and chemokine production, increased anti-inflammatory proteins, and attenuated tissue damage [12][13][14]. SBI has also been tested in a randomized controlled trial, an open label study and several case series in IBS-D patients [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%